2022
DOI: 10.3390/v14122605
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Titer Correlates with Omicron Infection in Vaccinated Healthcare Workers

Abstract: The advent of vaccines against SARS-CoV-2 has drastically reduced the level of hospitalization with severe COVID-19 disease in infected individuals. However, the diffusion of variants of concern still challenge the protection conferred by vaccines raised against the wild-type form of the virus. Here, we have characterized the antibody response to the BNT162b2 (Comirnaty) mRNA vaccine in patients infected with the Omicron variant. We analyzed a population of 4354 vaccinated healthcare workers (HCW) from 7 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
6
3
Order By: Relevance
“…We estimated a similar level of protection during the Delta period for the homologous (80%; two mRNA doses) and heterologous (89%; one dose of a viral vector vaccine and one dose of an mRNA vaccine) vaccination regimens when we applied the same threshold, or even about three‐times higher for the hybrid immunity group (97%). Conflicting results have been reported in the case of Omicron variant regarding the value of anti‐RBD IgG as a CoP 6‐8,23 . The reduction in neutralization titers observed for Omicron compared to previous variants 24 could indicate that infection can even occur shortly after the booster dose despite high binding antibody levels, 25 as observed in the present study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We estimated a similar level of protection during the Delta period for the homologous (80%; two mRNA doses) and heterologous (89%; one dose of a viral vector vaccine and one dose of an mRNA vaccine) vaccination regimens when we applied the same threshold, or even about three‐times higher for the hybrid immunity group (97%). Conflicting results have been reported in the case of Omicron variant regarding the value of anti‐RBD IgG as a CoP 6‐8,23 . The reduction in neutralization titers observed for Omicron compared to previous variants 24 could indicate that infection can even occur shortly after the booster dose despite high binding antibody levels, 25 as observed in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…A cohort study conducted in Denmark reported, more recently, an association between the level of anti‐spike IgG and the risk of breakthrough infection with Delta but not with Omicron BA.1 and BA.2 among fully vaccinated individuals 6 . However, other studies have reported an inverse relationship between anti‐spike IgG levels and the risk of breakthrough infection with Omicron BA.1 after the second dose of BNT162b2 vaccine, 7 or lower peri‐infection anti‐spike IgG levels in breakthrough cases compared to matched controls 8 . The inconclusive findings of the association between IgG levels and the risk of Omicron infection warrant further studies in individuals with different vaccination schedules to determine whether the CoP for Delta and previous variants of concern (VOCs), are effective with Omicron BA.1 and new Omicron subvariants such as XBB.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated a similar risk of infection during the Delta period for the homologous (two mRNA doses) and heterologous (one dose of a viral vector vaccine and one dose of an mRNA vaccine) vaccination regimens when we applied the same threshold, or even about three-times lower for hybrid immunity group. However, conflicting results have been reported in the case of Omicron variant regarding the value of anti-RBD IgG as a CoP (7)(8)(9)23). The reduction in neutralisation titres observed for Omicron compared to previous variants (24) could indicate that infection can even occur shortly after the booster dose despite high binding antibody levels (25), as observed in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…This is supported by a cohort study conducted in Denmark in which an association between the level of anti-spike IgG and the risk of breakthrough infection with Delta but not with Omicron BA.1 and BA.2 among fully vaccinated individuals (7). However, other studies have reported an inverse relationship between anti-spike IgG levels and the risk of breakthrough infection with Omicron after the second dose of BNT162b2 vaccine (8), or lower peri-infection anti-spike IgG levels in breakthrough cases compared to matched controls (9). Therefore, further studies in individuals with different vaccination schedules and hybrid immunity are needed to determine whether the CoP for Delta and previous variants of concern (VOCs), such as anti-RBD IgG, are effective with Omicron BA.1 and new Omicron subvariants.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation